Zika virus outbreak in the Pacific: Vector competence of regional vectors. - Elodie Calvez; Laurence Mousson; Marie Vazeille; Olivia O'Connor; Van-M; Françoise Mathieu-Daudé; Nicolas Pocquet; Anna-Bella Failloux; Myrielle Dupont-Rouzeyrol (Public Library of Science (PLoS), 2018)
BACKGROUND:In 2013, Zika virus (ZIKV) emerged in French Polynesia and spread through the Pacific region between 2013 and 2017. Several potential Aedes mosquitoes may have contributed to the ZIKV transmission including Aedes aegypti, the main arbovirus vector in the region, and Aedes polynesiensis, vector of lymphatic filariasis and secondary vector of dengue virus. The aim of this study was to analyze the ability of these two Pacific vectors to transmit ZIKV at a regional scale, through the evaluation and comparison of the vector competence of wild Ae. aegypti and Ae. polynesiensis populations from different Pacific islands for a ZIKV strain which circulated in this region during the 2013-2017 outbreak. METHODOLOGY/PRINCIPAL FINDINGS:Field Ae. aegypti (three populations) and Ae. polynesiensis (two populations) from the Pacific region were collected for this study. Female mosquitoes were orally exposed to ZIKV (107 TCID50/mL) isolated in the region in 2014. At 6, 9, 14 and 21 days post-infection, mosquito bodies (thorax and abdomen), heads and saliva were analyzed to measure infection, dissemination, transmission rates and transmission efficiency, respectively. According to our results, ZIKV infection rates were heterogeneous between the Ae. aegypti populations, but the dissemination rates were moderate and more homogenous between these populations. For Ae. polynesiensis, infection rates were less heterogeneous between the two populations tested. The transmission rate and efficiency results revealed a low vector competence for ZIKV of the different Aedes vector populations under study. CONCLUSION/SIGNIFICANCE:Our results indicated a low ZIKV transmission by Ae. aegypti and Ae. polynesiensis tested from the Pacific region. These results were unexpected and suggest the importance of other factors especially the vector density, the mosquito lifespan or the large immunologically naive fraction of the population that may have contributed to the rapid spread of the ZIKV in the Pacific region during the 2013-2017 outbreak.